Determining synthesis region of the single wall carbon nanotubes in arc plasma volume. (October 2016) - Fang, Xiuqi; Shashurin, Alexey; Teel, George; Keidar, Michael
Abstract: Arc discharge is one of the most efficient and environmental friendly method to synthesize Single Wall Carbon Nanotube (SWCNT). However, due to the ultra-fast synthesis procedure, localization of the SWCNT synthesis in an arc discharge plasma volume in situ has been a long standing problem. This relates to the ability of controlling volumetric synthesis of nanostructures in plasmas in general. In order to better understand the mechanism of the nanotube growth in plasma, we have developed an actuator driven high-speed system that is able to extract material from the arc plasma volume during the synthesis procedure. The majority of the SWCNTs produced using arc discharge method are semiconducting with diameter of about 1.5 nm. It is shown that the growth region of SWCNTs is between 3 mm and 11 mm away from the center of the arc discharge. Dependent on the origin, the length of SWCNTs increases non-monotonically up to 500 nm, while diameter and chirality only slightly depend on the growth position.